AN ANALYSIS OF AFFECTIVE MEANING AND IMAGERY IN SONG LYRICS OF TAYLOR SWIFT’S "THE TORTURED POETS DEPARTMENT” ALBUM - Maharani, Lupita; Julianti, Defi (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Affective meaning is related to how the feelings and attitudes of the writer are reflected in their communication. Besides affective meaning, the writer often use imagery to visualize the scene and understand the meaning of the song lyrics more deeply and connect with the emotions conveyed in the song lyrics. Thus, the researcher decided to conduct this research using Leech (1981), Larson (1984), and Abrams (1999) theory. This research aimed to find out types of affective meaning and imagery that occur in the song lyrics in Taylor Swift’s album entitled “The Tortured Poets Department”. The method used in this research was qualitative research method. The researcher identified 174 data of affective meaning; 41 data of positive meaning and 133 data of negative meaning. The researcher also found 167 data of imagery; 131 data of visual, 15 data of auditory, 3 data of tactile, 2 data of thermal, 2 data of olfactory, 2 data of gustatory, and 12 data of kinesthetic imagery.